Catullan Labyrinths in Vergilian Ecphrasis - Somfai, Péter (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
This study aims to investigate the intertextual connections of the labyrinth passage of Catullus 64 and the ecphraseis of Book 6 and 8 of Vergil’s Aeneid. The ecphrastic nature of these passages provides an opportunity to analyze the relations of these texts by taking the phenomenon of intermediality into consideration. In addition, my objective is to examine the role of ecphraseis within the narratives of Catullus 64 and the Aeneid, and to analyze how the poetic and thematic dimensions of the depicted artworks extend to the framing texts, which can thus be interpreted as peculiar labyrinths, that of a textual kind. Bearing in mind that ecphraseis can provide an interpretative framework for their wider context, it may be of critical significance that the labyrinth gets evoked in those books of the Aeneid that focus on Roman history in close connection with Augustan ideology.